The Probe Team [episode no. 281] - Bayle, Anna (Probe Productions, 1994)
Impasse deals with the issue on Total Log Ban bill. Duty-Free Philippines competing with other department stores is protrayed in Fearing Duty-Free. An exclusive interview of the most successful ramp model is seen in the lasr part.